Prelacteal feeding practice and its associated factors in Afghanistan: insights from the 2022–2023 multiple indicator cluster survey - Stanikzai, Muhammad Haroon; Tawfiq, Essa; Dadras, Fateme; Ezadi, Zainab; Jafari, Massoma; Fazli, Najibullah; Wasiq, Abdul Wahed; Dadras, Omid (BioMed Central, 2026)
Background
Prelacteal feeding (PLF), which refers to giving liquids or non-breast milk food to infants within 3 days of birth, can adversely affect neonatal health and survival. Despite its recognized health risks, PLF remains prevalent in many low- and middle-income countries (LMICs), including Afghanistan, where evidence on its determinants is limited. Thus, this study aimed to determine the prevalence and associated factors of PLF practice in Afghanistan.
Methods
We analyzed data from 11,964 ever-married women aged 15–49 years with a live birth in the previous two years. PLF was defined according to the MICS convention. Multivariable logistic regression models were used to identify factors associated with PLF, accounting for survey design and sampling weights. Interaction terms were tested for (1) place of delivery and household wealth and (2) private facility and cesarean section.
Results
The prevalence of PLF was 33.3%. The odds of PLF practice were lower in women with primary (AOR 0.72; 95%CI 0.58–0.89) and secondary/higher (AOR 0.73; 95%CI 0.58–0.92) education and in women with early initiation of breastfeeding (AOR 0.37; 95%CI 0.33–0.42). Conversely, women residing in rural areas (AOR 1.27; 95%CI 1.06–1.54), those delivering in private health facilities (AOR 1.38; 95%CI 1.11–1.72), women who had cesarean section (AOR 1.72; 95%CI 1.31–2.25), and those in middle to higher wealth quintiles were more likely to practice PLF. Interaction analyses showed that the positive association between wealth and PLF was concentrated among women delivering in private facilities, with private-sector births exhibiting consistently elevated PLF across all wealth groups. The interaction between private delivery and cesarean section was not significant, indicating that high PLF levels in private facilities were not driven by cesarean rates.
Conclusion
One in three Afghan newborns receives prelacteal feeds. Private-sector maternity care, socioeconomic gradients linked to facility choice, cesarean delivery, rural residence, and delayed breastfeeding initiation are key drivers of PLF. Strengthening breastfeeding support in private facilities, promoting early initiation of breastfeeding, and enhancing maternal education—particularly in rural and higher-income communities—are essential to reducing PLF in Afghanistan.